Profiles of traditional farms: soil texture, total inorganic N and bacteria-producing estate - Yuni Puji Hastuti; Iman Rusmana; T. Widiyanto (Jurnal Akuakultur Indonesia)
Pond traditional system is the pond in still activity with a symple management system.  This activity indicated by low technology and relatively low production level.  Aquaculture activities in traditional pond not loss from nitrification and denitrification prosess, however this process is more low production rather than semiintensive and intensive system. This study aims to observe abundance of bacteria nitrification along with changes soil texture, and N-organic in the soil of traditional pond. Chemical and biological analyses were done using spectroscopy and Most Probable Number methods to determine the amount of nitrite and ammonium production of bacteria.  Based of the result, each stratum traditional ponds have relatively similar abundance in nitrite producing bacteria of 7.08-7.47 Log CFU/g.  Increasing abundance in ammonium producing bacteria was found in all stratum, range from 5.63 Log cfu/g to 8.12 Log cfu/g. From the first day of preparation, traditional ponds have a lot of nitrite and ammonium producing bacteria.